Body mass index and healthy lifestyle practices among Peruvian university students: a comparative study among academic discipline - Saintila, Jacksaint; Calizaya-Milla, Yaquelin E.; Carranza-Cubas, Sandra P.; Serpa-Barrientos, Antonio; Oblitas-Guerrero, Susan M.; Ramos-Vera, Cristian (Frontiers in Nutrition, 2024)
Background: Excess body weight and an unhealthy lifestyle are a risk factor for noncommunicable diseases. University students are susceptible to unhealthy habits and obesity. This study compared body mass index (BMI) and healthy lifestyle practices among university students from four academic disciplines: Health Sciences, Business Sciences, Human Sciences and Education, and Engineering/Architecture. Methods: A cross-sectional study was carried out using a sample of 6,642 university students selected by non-probability convenience sampling. The Diet and Healthy Lifestyle Scale (DEVS), the Peruvian validation of the Vegetarian Lifestyle Index (VLI), was used to assess healthy lifestyle practices. Results: Students in the areas of Business Sciences and Engineering/Architecture had a higher BMI than their peers in Health Sciences (B = 0.35, 95% CI: 0.15 - 0.56 and 0.32, 95% CI: 0.13 - 0.52; p = 0.001). Additionally, these students tended to adopt less healthy lifestyle (B = -0.11, 95% CI: -0.20 - -0.01 and -0.09, 95% CI: -0.18 - -0.00; p < 0.05) compared to those in Health Sciences. Conclusion: Although students of Health Sciences and Human Sciences and Education exhibited healthy lifestyle patterns, there is a clear need to improve eating and living habits in general among the university population to mitigate the risk factors associated with non-communicable diseases.